2020
DOI: 10.1002/cb.1818
|View full text |Cite
|
Sign up to set email alerts
|

How does green advertising skepticism on social media affect consumer intention to purchase green products?

Abstract: Underpinned by the stimulus–organism–response model, this study explores the underlying mechanism through which green advertising skepticism on social media affects consumer green purchase intention. It also investigates the boundary factors that moderate this indirect relationship. Performing structural equation modeling on data collected from an online survey on Sina Weibo, this study finds that green advertising skepticism on social media negatively affects green purchase intention through the mediation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 55 publications
4
97
0
4
Order By: Relevance
“…This study combines the two research collection methods and obtains scientific data in the fastest way. The samples collected are representative, and the sample distribution is similar to the sample distribution of prior green advertising and green consumption research (Luo, Sun, Shen, & Xia, 2020).…”
Section: Methodsmentioning
confidence: 92%
“…This study combines the two research collection methods and obtains scientific data in the fastest way. The samples collected are representative, and the sample distribution is similar to the sample distribution of prior green advertising and green consumption research (Luo, Sun, Shen, & Xia, 2020).…”
Section: Methodsmentioning
confidence: 92%
“…In addition, other researchers investigated the influence of individual values [ 4 ] and environmental concern [ 6 ] on consumer green consumption. From the perspective of advertising, Sun and Wang (2020) [ 15 ] found that social media can positively affect intention, while green advertising skepticism may reduce it [ 16 ]. However, most of the previous research only explained why consumers prefer or refuse green products from the point of consumers themselves, instead of investigating what method or advertising enterprises can use to promote green products.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sun (2020) [ 15 ] suggested that social media marketing positively affected subjective norms and product knowledge, which, in turn, increased purchase intention for green products. However, green advertising skepticism on social media may reduce this preference [ 16 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…When such situational causes are apparent, extrinsic attributions are more likely to be made (Kelley & Michela, 1980). In addition, although corporate prosocial values are considered as important in ethical consumer decision making (Shaw, Grehan, Shiu, Hassan, & Thomson, 2005), consumers tend to perceive prosocial marketing actions as company‐focused and manipulative, and are therefore inclined to question the sincerity of corporate motives (Heath & Chatzidakis, 2012; Luo, Sun, Shen, & Xia, 2020).…”
Section: Introductionmentioning
confidence: 99%